SISTEM INFORMASI POTENSI WISATA DI KABUPATEN KOLAKA TIMUR BERBASIS WEB - Muh. Alim Zulkifli Kifli (Program Studi Informatika Universitas Teknologi Sumbawa, 2021)
East Kolaka Regency is one of the regencies in Southeast Sulawesi Province which has quite a lot of tourism potential areas. However, there are still many tourists who do not know the tourism in East Kolaka Regency. The lack of knowledge about tourism is caused by information about tourist attractions that is still minimal and has not been published properly. In this case, to assist related parties and tourists in getting to know tourism in East Kolaka Regency, a website was built that can provide detailed information about tourism and routes to tourist attractions in the East Kolaka Regency area. To provide route information, use Google Maps which will access the current location of the user towards the direction of the tourist spot they want to visit. With this website, it is hoped that it can help tourists recognize the tourism potential in the East Kolaka Regency and also help the managers of tourist attractions in introducing tourist areas in East Kolaka Regency